Interlinking Developer Identities within and across Open Source Projects: The Linked Data Approach. (10th June 2013) - Iqbal, Aftab; Hausenblas, Michael
Abstract : Software developers use various software repositories in order to interact with each other or to solve related problems. These repositories provide a rich source of information for a wide range of tasks. However, one issue to overcome in order to make this information useful is the identification and interlinking of multiple identities of developers. In this paper, we propose a Linked Data-based methodology to interlink and integrate multiple identities of a developer found in different software repositories of a project as well as across repositories of multiple projects. Providing such interlinking will enable us to keep track of a developer's activity not only within a single project but also across multiple projects. The methodology will be presented in general and applied to 5 Apache projects as a case study. Further, we show that the few methods suggested so far are not always appropriate to overcome the developer identification problem.